Application of 35NCD 16 Steel Under Cyclic Loading by an Elastoplastic Model - Chebbab, Brahim; Djeziri, Mourad (Manufacturing Technology Journal, 2024)
The purpose of this paper is to study an application of the 35NCD 16 steel by a model generalizing the isotropic and kinematic strain hardening laws. The model in question is represented by a field of strain hardening moduli corresponding to the introduction of the configuration of the flow surfaces. Each flow surface is characterized by its constant elastoplastic modulus, its normal unit vector, its radius and its center coordinates. For cases of uniaxial or multiaxial (complex) loading, in particular for cases of cyclic loading or unloading, the instantaneous configuration can be determined by the position and dimensions of the flow surfaces, determining the strain increment for each strain incre-ment.
Keywords: Cyclic plasticity; Three-dimensional elastoplasticity; Incremental elastoplasticity; Plastic flow surface